The Properties Study of Mangrove Fruit Flour Composited with Taro and White Uwi Tubers - Jariyah Jariyah; Ulya Sarofa; Rawiri Yunia Ratna (Universitas Dr Soetomo, 2020)
This research is a part of research on the study of the glycemic index value of biscuit products from mangrove fruit flour with flour from various of tubers. The tubers used in this study were taro and white uwi. The types of mangrove fruit used were pedada and lindur. The starch content in taro tubers and white uwi can be used to make biscuits. It is known that both pedada (Sonneratia caseolaris) and lindur (Bruguiera ghymnorhiza) flour have anti-diabetic and anti-cholesterol properties. This study aims to analyze the characteristics of the biscuits from the formulation of a mixture of mangrove fruit flour with taro and white uwi tubers. This study used a one-factor completely randomized design with 10 levels of treatment, namely the proportion of mangrove fruit flour types of pedada and lindur and taro and white uwi tuber flour with the formula 0: 100, 10:90, and 20: 80. Biscuit product analysis parameters include proximate, organoleptic analysis, and glycemic index. Measurement of the glycemic index value was carried out in vivo using 22 respondents normal human, healthy, with a blood glucose of 80-100 mg / dL. Blood draws were carried out for 120 minutes at 30-minute intervals. The best biscuits were obtained in the formulation of pedada fruit : taro flour (20: 80), with criteria 84.07%, of yield, 3.72% of moisture content, 3.45% of ash, 4.33% of protein, 7.16% of fat, carbohydrates of 81.34%, 64.39% of starch, the dietary fiber content of 7.69%. Organoleptic test results showed 5.69 of color, the taste of 6.68, texture of 6.54, aroma of 7.13. In vivo test results obtained glycemic index values of 51.46, and glycemic load of 12.90